2015
DOI: 10.1186/s12911-015-0220-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a biopsychosocial educational internet-based intervention on pain, dysfunction, quality of life, and pain cognition in chronic low back pain patients in primary care: a mixed methods approach

Abstract: BackgroundLow back pain is the highest reported musculoskeletal problem worldwide. Up to 90 % of patients with low back pain have no clear explanation for the source and origin of their pain. These individuals commonly receive a diagnosis of non-specific low back pain.Patient education is a way to provide information and advice aimed at changing patients’ cognition and knowledge about their chronic state through the reduction of fear of anticipatory outcomes and the resumption of normal activities. Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…The following approaches were mentioned as underpinning or rationales for the intervention: mindfulness [28], person-based approach [31], and self-management principles (not specified further) [29]; and tools such as goal setting [33] and information on pain and pain etiology [32,36]. Finally, 2 studies also reported that the advice given to participants was based on treatment guidelines, either evidence-based or recommendations from Governmental Institutes [27,37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following approaches were mentioned as underpinning or rationales for the intervention: mindfulness [28], person-based approach [31], and self-management principles (not specified further) [29]; and tools such as goal setting [33] and information on pain and pain etiology [32,36]. Finally, 2 studies also reported that the advice given to participants was based on treatment guidelines, either evidence-based or recommendations from Governmental Institutes [27,37].…”
Section: Resultsmentioning
confidence: 99%
“…Better consistency in choice of outcome measures was seen in the 3 RCT protocols of planned RCTs [27,31,36]. We expect that these trials will provide more useful information and data for future meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…It is important for nurses and clinicians to evaluate all dimensions of the pathology since only by using a biopsychosocial approach can we understand the patient's condition and intervene satisfactorily, thus avoiding the progression of high chronicity with its associated socio-sanitary costs given the high perceived disability that we report in this work (Valenzuela-Pascual et al, 2015).…”
Section: Implications For Primary Carementioning
confidence: 95%
“…The Internet has become a leading resource for the dissemination of health information to the public (Ahmed et al., ; Bailey et al., ; Demetriades et al., ; Nielsen et al., ; Palermo et al., ; Valenzuela‐Pascual et al., ). Over 3.3 billion people access the Internet worldwide (Miniwatts Marketing Group, ) and 80% of users within the United States are estimated to access health information online (Fox, ).…”
Section: Introductionmentioning
confidence: 99%
“…Popularity of the search term ‘lower back pain’ within the Google search engine has been consistently increasing (Google, ), compared to other related search terms that are specific to the lower back (Google, ), an observation that reflects the public trend towards seeking freely available online LBP information. Education is a critical aspect to LBP management (Dagenais et al., ); therefore, it seems reasonable to suggest that increased access to health information could aid in the management of such a burden, yet LBP disability remains substantially high as online access to health information continues to rise (Ahmed et al., ; Bailey et al., ; Demetriades et al., ; Nielsen et al., ; Palermo et al., ; Valenzuela‐Pascual et al., ). An understanding of current online LBP information and how its content compares to a current understanding of LBP is critical if the Internet is to become an effective educational resource in LBP management.…”
Section: Introductionmentioning
confidence: 99%